“Shadows Like to Thee”: Modern Writers on the Character of William Shakespeare - Hickman, Alan Forrest (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
A swarm of books boasting William Shakespeare as a central character have hit the bookstands in recent years. The question is, why? In some books, he is rather insipid, as if his brand is too hot to tamper with, and he is reduced to the status of a sacred cow. In other books, he is too busy fighting for truth and justice to be bothered with taking up the quill, while in others, he is an opportunistic “Shake-scene” who has no qualms about “beautifying” himself with his contemporaries’ feathers. I propose to look at such works in the aggregate and determine the basic physical and character traits that modern scribes attribute to our Will. My journey will take me primarily to novels (of the historical fiction school), but I shall be stopping along the way to consider works in other media, including a recent TV series, that also features the Bard. Among the novelists included in my study are Patricia Finney (The James Enys Mysteries), Rory Clements (The John Shakespeare Mysteries), Benet Brandreth (The William Shakespeare Mysteries), and Leonard Tourney (The Mysteries of Shakespeare).